EFEKTIVITAS PELAKSANAAN PROGRAM BANTUAN PANGAN NON TUNAI SEBAGAI UPAYA PENANGANAN FAKIR MISKIN DI DESA PANYIPATAN KECAMATAN PANYIPATAN KABUPATEN TANAH LAUT - Widiati (stiatabalong.ac.id, 2023)
The Non-Cash Food Assistance Program or (BPNT) is a social program organized by the government for underprivileged communities, Non-Cash Food Assistance (BPNT) is distributed in the form of non-cash or electronic money where this assistance can only be used to buy food in e-Warong. The purpose of this study was to determine the Effectiveness of the Implementation of the Non-Cash Food Assistance Program as an effort to deal with the poor in Panyipatan Village, Panyipatan subdistrict, Tanah Laut Regency. This study uses a qualitative descriptive method and to collect data using interviews for primary data and observation and documentation as secondary data. Informants selected in this study used a purposive technique or technique with a purpose, totaling 12 people consisting of 3 (three) men and 9 (nine) women. This study uses 5 indicators, namely program understanding, target accuracy, timeliness, goal achievement and real change. The research results from indicators (1) program understanding, in the Panyipatan community the BPNT program can be said to be good, but on the other hand in indicators (2) target accuracy and indicators (3) timeliness, there are still things that need to be improved in this program, for indicators (4) to achieve the goal, the current BPNT program has been realized and implemented well. and finally indicator (5) real change, the impact felt by the community (Beneficiary Families) is greatly assisted, especially in terms of daily food needs so that it can provide balanced nutrition to (Beneficiary Families) and reduce excessive expenditure burdens. Keywords: Effectiveness, BPNT implementation, Handling the Poor